(untitled) (Context: Journal of Interdisciplinary Studies, 2023)
This paper draws attention to different concepts of the classification of sciences and their relationships based on the most famous Ottoman encyclopedic works from the 16th century, and points to the connection of the concept of classification of sciences with the preference of particular sciences and scientific disciplines in education with the development of intellectual thought and circles within the Empire. The works Miftāḥ alsaʿāda wa miṣbāḥ al-sayyāda fī mawḍūʿāt al-ʿulūm by Taškoprī-zāde, in Arabic, and Netāʼicü l-fünūn ve meḥāsinü l-mutūn by Malkarali Nevʻī, in Turkish, are among the most famous encyclopedic works in the Ottoman literary tradition in the 16th century that deal with the classification of sciences. To provide a more complete analysis of the issue of conflict and/or addition of the concept of classification of knowledge and sciences among the Ottomans in the 16th century, we attempted to highlight the cultural and social context of the creation of the aforementioned works, as well as to explain in detail the connection between the concept and the content of works dealing with the classification of sciences.